18. SLEEP QUALITY AMONG ADOLESCENTS AGED 15-17 IN DA NANG, 2024: A CROSS-SECTIONAL STUDY (Tạp chí Y học Cộng đồng, 2024)
Objective: (1) To determine the prevalence of sleep disorders among adolescents aged 15 to 17 years; (2) To analyze factors associated with sleep quality in adolescents aged 15 to 17 years.Design, Setting, and Participants: Cross-sectional descriptive study. Among Adolescents aged 15-17 years old at Hoa Vang High School we collected 737 eligible participants for the study.Main Outcome Measures: Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Associations between Sleep quality were evaluated with multivariable conditional logistic regression controlling for gender, exercise habits, sleep hygiene habits, pressure and expectations about academic performance (parental expectations, pressure for achievement, completing homework, extra classes).Results: The sleep quality of adolescents aged 15-17 at Hòa Vang High School is alarmingly low, with PSQI scores averaging 5.5±3.3 for 10th-grade students (15 years old), 6.1±3.3 for 11th grade (16 years old), and 6.4±3.5 for 12th grade (17 years old). The findings show that 47.5% of students have poor sleep quality, with a trend of worsening sleep quality with age. Additionally, most study participants go to bed relatively late. Factors associated with poor sleep quality include being female, excessive phone use before bed, academic pressure, homework load, and hours spent on daily extra classes. Addressing this issue requires appropriate sleep education and awareness for both students and parents.Conclusion: This study indicates an alarmingly low level of sleep quality among students at Hoa Vang High School, with a significant proportion experiencing poor sleep quality, and highlights several associated factors.
Keywords: sleep disorder; sleep quality; adolescents; 15-17 years old; Da Nang; Hoa Vang High School